TPAC: A 0.18 micron MAPS for digital electromagnetic calorimetry at the ILC - Ballin,JA; Coath,RE; Crooks,JP; Dauncey,PD; Levin,B; Lynch,M; Magnan,AM; Mikami,Y; Noy,M; Miller,O; Rajovic,V; Stanitzki,M; et al. (2008)
For the ILC physics program, the detectors will need an unprecedented jet energy resolution. For the electromagnetic calorimeter, the use of a highly granular silicon-tungsten calorimeter has been proposed. We have developed a Monolithic Active Pixel-based readout for such a calorimeter, which will have extremely fine granularity and will make use of a digital readout. The first generation chip (TPACl) implements a 168x168 array comprising 50x50 μm 2 pixels. Each pixel has an integrated charge pre-amplifier and comparator. TPACI has been manufactured in the 0.18 μm INMAPS process which includes a deep p-well. We present results of the performance of the TPACI chip together with comparison to simulations and give an outlook to the second generation chip. © 2008 IEEE.